SECTION OF ALL-RUSSIAN SCIENTIFIC SOCIETY OF CARDIOLOGISTS ON RATIONAL PHARMACOTHERAPY IN CARDIOLOGY (Столичная издательская компания, 2015)
Section of All-Russian Scientific Society of Cardiologists on Rational Pharmacotherapy in Cardiology.